Parâmetros de colheita mecanizada na qualidade de sementes e grãos armazenados de feijão comum - Soncela, Rodrigo Ferreira (2011)
With the expansion of the bean, the mechanized harvesting is becoming increasingly necessary, both due to shortage of manpower, on the increase of crop yield. Therefore, it becomes essential to have knowledge of the variables involved in this operation. So, in this context, the aim of this study is to assess changes in quality of seeds and grains of beans, stored in accordance with parameters of mechanical harvesting. The experiment was conducted in a commercial area in Santa Tereza do Oeste Paraná, using, for the harvest IAPAR 81, combine harvester, with "bean kit" and cylinder axial (adapted). The culture was initiated in the 2009/2010 agricultural year, using line spacing of 0.45 m m-1 14 plants and cultural practices were applied in order to control insects, diseases and weeds. To harvest, harvest times were tested (8, 12 and 16 h), cylinder rotation (300, 340 and 385 rpm) and the harvester forward speed (4, 5 and 6 km h-1). We evaluated the water content, purity, loss and damage to seeds and germination percentage. The grains and seeds harvested were stored and the evaluations done at 0 (control), 45, 90 and 180 days. For the assessment of technological quality, tests were conducted of the cooking time, water absorption before cooking, and the evaluation of the germination, moisture content, weight of 100 seeds. The experiment was conducted in a randomized design and layout of sub-sub divided plot (3 x 3 x 3 - harvesting times, speed and cylinder rotation) with four replicates and storage was the same scheme of analysis in harvest, but evaluated at each storage time. The results were submitted to ANOVA, and comparisons of means were carried out by Tukey test at 5% significance), using the program SISVAR. The parameters evaluated influenced on the quality of grains and seeds. Crop losses were lower at 12 and 4 p.m., at lower rotation speeds and cylinder displacement of the harvester. The purity of seeds was lower at 4 p.m. with a lower rotation speed intermeeting. Mechanical damage was not significant at harvest, with the variation of the parameters for collection, but may have influenced the quality parameters of grain and seeds. There was a gradual increase in the percentage of germination of bean seeds during storage, and there may be an inverse relationship with water content. Damage occurred during harvesting may have influenced the increase of cooking time and reduced water absorption, since there were differences of these parameters within each storage time. No relationship was observed between percentage of water absorption in the grain and cooking time, given that little variation in the first parameter was observed during storage, unlike the cooking time, in which the changes were remarkable